Computational evaluation of micropores wetting effect on the removal process of CO2 through the membrane contactor - Abdulrahman Sumayli; Zakarya Ahmed; Vicky Jain; R. Roopashree; Anjan Kumar; Aditya Kashyap; Mukesh Kumari; Sofia Gupta; G. V. Siva Prasad; Munthar Kadhim Abosaoda (Scientific Reports)
Abstract In the current years, gas–liquid membrane contactors (GLMCs) have been introduced as a promising, versatile and easy-to-operate technology for mitigating the emission of major greenhouse contaminants (i.e., CO2 and H2S) to the ecosystem. This paper tries to computationally study the role of membrane pores wettability on the removal performance of CO2 inside the HFMC. To fulfill this purpose, a mathematical model based on finite element procedure (FEP) has been employed to solve the momentum and mass transport equations in the partial-wetting (50% wetting of micropores) and non-wetting (0% wetting of micropores) modes of membrane during operation. Additionally, a comprehensive simulation was ensembled to predict the results. In this research, 2-amino-2-methyl-l-propanol (AMP) has been employed as a relatively novel alkanolamine absorbent to separate CO2 form CO2/N2 mixture. Analysis of the results implied that the wetting of membrane micropores significantly deteriorated the removal efficiency due to the enhancing mass transfer resistance towards transferring CO2 (75% in the non-wetting mode > 8% considering 50% wetting of micropores).